Analysis of Entropy Generation and Potential Inhibition in an Aeroengine System Environment - Xiaojing Liu; Shuiting Ding; Tian Qiu; Chuankai Liu; Peng Liu; Guo Li; Xiaozhe Zhang (International Journal of Aerospace Engineering)
From a system perspective, the entropy generation of an aeroengine is directly related to the thermal efficiency when the Brayton cycle pressure ratio and maximum temperature remain constant. The lower the entropy generation of the engine is, the higher the thermal efficiency. However, the secondary air system of the engine generates a large quantity of entropy compared to the components of the main flow channel, because the irreversible losses of the internal flow and heat exchange between the air system components generate considerable entropy within the system. In this study, the theoretical method is used to build entropy generation model for different characteristics of air system components during the aerothermal process. In this basis, an integrated model of the whole engine is introduced to identify the key components for entropy generation in the system environment. The results show that the labyrinth at outlet of unloading cavity is recognized as the one that generates the most entropy in the entire aeroengine system, and the total entropy generation of the system is highly related to this component. Besides, in the system environment, entropy generation is the sum of the local entropy generated by the components and the total entropy generated by mixing of airflows in each component. High local entropy generated by components does not necessarily result in a high system entropy production, and vice versa. Therefore, when the minimum system entropy generation is the design goal, the most critical operations for entropy generation should be identified according to the corresponding sensitivity and parameter variation range, and the design should be improved accordingly.